Various forestry Use Objectives - Bhadran, C. A. R. (Indian Forester, 1966)
by affording spare-time or supplemental employment, also ready funds in times of need besides introducing additional money returns regularly. Forestry can also have a direct effect on national economy, by providing raw-material for industry, earning or saving foreign exchange and often inducing developments in other sectors. Where forest production can compete, forestry can even wrest land from other forms of land use. Even otherwise, any rational land-use policy must recognise that forestry has to prevail over a proportion of all land in view of the basic productive and protective function it performs. In assessing the objectives of forestry use for grazing, for wild life conservation and for recreation, the indirect benefits accruing to the people must be recognised as of far greater value than the direct (monetary) returns obtained by the forest administration. Such benefits include improved animal husbandry aesthetic values of forest scenery and forest life, improved health of the people, etc. The apparently incompatible elements between these objectives and those of production and protection can be harmonised by necessary re-adjustments and regulation. Forest influences on the environment (its climate, the conservation of soil and moisture, the regulation of stream-flow and water supply) are of paramount importance even if they are intangible. The perpetuation of such influences must remain a first objective of Forestry Use; and, forest management practices (for production of any kind) will, wherever so required: have to be re-adjusted accordingly. The claims of forestry will be greatly strengthened If a satisfactory method can be evolved for the evaluation of these intangible benefits. Forestry could even private investments where the objectives involve short-term production but in most other cases Forestry has to remain, by and large, a public undertaking; or, private forestry will require to be subsidised by the State. Investments even of public funds and setting apart land for forestry can be fully justified when various forestry-use objectives could be achieved in harmony from the same forestry undertaking. The problems likely to arise (in harmonising) would include - (1) quantitative evaluation of the relative importance of objectives (feasible targets), (2) assessment of the value (in economic terms) of indirect and of intangible benefits, (3) Needs. Of Research and experiment for improving techniques, and (4) revision of National forest policies and adoption of quantitative National plans for forest development.